Advances in robotic-assisted treatments for renal cell carcinoma. Issue 5 (September 2016) - Maurice, Matthew J.; Ramirez, Daniel; Kaouk, Jihad H.
Abstract : Purpose of review: Robotic techniques and technology for renal cell carcinoma surgery are constantly evolving to improve outcomes. This article reviews new knowledge and recent developments in robotic surgery for renal cancer. Recent findings: The long-term oncological efficacy of robotic partial nephrectomy for small renal masses has been confirmed. The greater relative importance of volume loss vs. ischemia duration in predicting long-term renal function after partial nephrectomy is now established, and the robotic technique may facilitate volume preservation. The feasibility of robotic radical nephrectomy with inferior vena cava tumor thrombectomy is being investigated. Robotic laparoendoscopic surgery offers cosmetic benefits compared with multiport technique, but technical constraints have limited widespread adoption. Cost reduction in robotic surgery is an emerging area of interest. Lastly, new purpose-built robotic systems are being developed to optimize single-site robotic surgery. Summary: Recent advances in robotic surgery for renal cancer include optimization of renal functional outcomes after partial nephrectomy, application of robotic surgery to locally advanced disease, minimization of invasiveness, cost reduction, and new robotic single-site surgery technology.